How Investment Mediates Infrastructure Effect on Economic Growth in Indonesia - Irwandi, Herwin; Jamal, Abd; Nasir, Muhammad (Grimsa Journal of Business and Economics Studies, 2025)
The availability of adequate infrastructure is one of the important foundations in encouraging investment and economic growth in a country. In Indonesia, over the last ten years, infrastructure development has become one of the main priorities to improve competitiveness and public welfare. This study aims to analyze the effect of the availability of road, electricity, and telecommunications infrastructure on investment and economic growth in Indonesia. The analysis uses panel regression analysis and path analysis methods in 34 provinces during the period 2014-2023. The research findings show that road infrastructure has no effect on economic growth, electricity infrastructure has a positive and significant effect on economic growth, while telecommunications infrastructure has a negative and significant effect on economic growth. Other findings show that investment partially mediates the effect of electricity and telecommunications infrastructure on economic growth; however, it does not mediate the effect of road infrastructure on economic growth. For this reason, the government needs to prioritize the development of electricity and telecommunications infrastructure because of its significant contribution to economic growth. Further evaluation and adjustment of road infrastructure policies are needed. Increasing investment, especially in sectors related to electricity and telecommunications infrastructure, also needs to be encouraged because it has a positive impact on economic growth.